EFFECTIVENESS OF VAGINAL HYGIENE EDUCATION AND RED BETEL LEAF DECORATIONS ON THE MANAGEMENT OF FLOUR ALBUS IN ADOLESCENT FEMALES AT THE HARAPAN BUNDA SEJAHTERA CLINIC - Marni Br Karo; Ijah Ijah; Friska Junita (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Adolescent girls are at high risk of experiencing vaginal discharge. Efforts that can be made to overcome the problem of vaginal discharge in adolescent girls are through vaginal hygiene education and also the provision of red betel leaf decoction. The purpose of this study was to determine the effectiveness of vaginal hygiene education and red betel leaf decoction on the management of vaginal discharge in adolescent girls at the Harapan Bunda Sejahtera Clinic, Bekasi Regency in 2024. The method used was a pre-experimental design with a one-group pretest-posttest. The population of adolescent girls with vaginal discharge, a sample of 45 people, purposive sampling technique, statistical test paired t test. The study showed that the incidence of vaginal discharge in adolescent girls before being given vaginal hygiene education and red betel leaf decoction was found that all 45 people (100%) experienced vaginal discharge, and after being given vaginal hygiene education and red betel leaf decoction, the majority did not experience vaginal discharge, 42 people (93.3%). There was effectiveness of vaginal hygiene education and red betel leaf decoction on the management of vaginal discharge with a p-value of 0.001. Red betel leaf decoction can treat vaginal discharge (fluor albus) because it contains flavonoids, saponins, tannins, and alkaloids, which act as antiseptics and anti-inflammatories, suppressing bacterial and fungal growth and relieving itching, irritation, and discomfort. Vaginal hygiene education and red betel leaf decoction are effective treatments for vaginal discharge in adolescent girls.